2020
DOI: 10.3145/epi.2020.jul.15
|View full text |Cite
|
Sign up to set email alerts
|

Gender disparities in UK research publishing: Differences between fields, methods and topics

Abstract: Gender disparities persist in UK research, with female minorities in most science, technology, engineering and mathematics (STEM) subjects but female majorities in others. The nature of the gender disparity differences between subjects needs to be understood if effective remedial actions are to be targeted at STEM subjects suffering from a lack of women, in contrast to other subjects without shortages. Evidence from the USA suggests that women engage more in people-related subjects, qualitative methods, veteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…In South Africa, women tend to be underrepresented in fields such as engineering, mathematics and physics and 'overrepresented' in fields such as the life and health sciences (notably nursing), social work, psychology, education and the like. 2,3 In Table 2, we see that there has been an increase in the share of female authors across all six broad science domains from 2005 to 2020; but the table also shows that female authors produced 48% of publications in the health sciences in 2020, compared to only 20% in engineering. Although the share of women authors in engineering is the lowest among the science domains, Prozesky and Van Lill 4 found that women in that field constitute only 20% of its research capacity.…”
Section: Gender Race and Scientific Field Of Authorsmentioning
confidence: 97%
“…In South Africa, women tend to be underrepresented in fields such as engineering, mathematics and physics and 'overrepresented' in fields such as the life and health sciences (notably nursing), social work, psychology, education and the like. 2,3 In Table 2, we see that there has been an increase in the share of female authors across all six broad science domains from 2005 to 2020; but the table also shows that female authors produced 48% of publications in the health sciences in 2020, compared to only 20% in engineering. Although the share of women authors in engineering is the lowest among the science domains, Prozesky and Van Lill 4 found that women in that field constitute only 20% of its research capacity.…”
Section: Gender Race and Scientific Field Of Authorsmentioning
confidence: 97%
“…Qualitative research methods are more likely to be used by female scholars than male scholars in India (Thelwall, Bailey, Makita, et al, 2019), the USA (Thelwall, Bailey, Tobin, & Bradshaw, 2019) and the UK (Thelwall, Abdoli, Lebiedziewicz, & Bailey, 2020), so the increasing share of female-authored research (e.g., Thelwall, 2020) may have generated a greater preference for qualitative methods in academia overall, a second order effect.…”
Section: Reducing Gender Inequalities In Academiamentioning
confidence: 99%
“…Only by uncovering the micro-mechanisms actually producing the gender differences observed on the macro level can effective measures be proposed to mitigate them. Our results indicate that the sorting of female and male scientists into different fields and topics [which has been shown, for example, by 32 , 47 , 48 ] is one of the most important mechanisms producing gendered citation patterns on the macro level. Therefore, one should in particular research the mechanisms underlying gendered specializations in research topics (so-called “horizontal segregation”), whether due to self-selection or sorting by gatekeepers.…”
Section: Discussionmentioning
confidence: 64%